Prospect and challenges of forest conservation extension for sustainable rural development: the experience of public extension services in Southwestern Nigeria (2006)
Implementing sustainable development and meeting the food needs of world's increasing population demand national and international investment in research and extension. Before fruitful investment can be guaranteed, inventory of the present status of the object of investment is imperative. This study examined the present status of public extension network in southwestern Nigeria with a view to ascertain its readiness as a learning organization for forest conservation information. Purposive and multistage random sampling (MRS) techniques were used to select three study sites -Oyo, Osun and Ondo States. Thirty management staff of protected areas and the extension staff of state's MANR in each of the three study sites earlier selected were randomly interviewed using structured questionnaire. Data generated were analyzed using descriptive and inferential statistics. The study revealed that an average of 60.26% of the extension personnel had a degree with the number of degree holders highest among respondents from Osun State, but less than half (41.99%) of the extension personnel in Southwestern Nigeria has over 10 years experience. Also, the capacity of government change institutions in the study area is inadequate to meet the demands of information dissemination on forest conservation; some (not all) of the government change agents in the study area are capable communicators although imbued with persuasion theories; and the conditions of service of the personnel of government change institutions is not conducive for optimum service. Thus, the need for a complete overhauling of the entire public learning institutions in the study area is imperative, most especially by re- training the personnel.